Three-Phase Inverter for High Speed Induction Motor - Veselý, Petr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This work deals with designing a power part of a three-phase inverter for induction motor. It contains choosing of some important parts such as IGBT modules or drivers, which depends on parameters, that are mentioned or calculated. Also a schema is included. General principle and brief theory is described in this paper too.
Keywords: IGBT; Three-phase inverter; induction motor